Epidemiological characteristics of bovine besnoitiosis (Besnoitia besnoiti) in a beef cattle farm: a cross-sectional serological assessment - Coelho, Joana; Domingues, Joana; Waap, Helga; Stilwell, George (Frontiers in Veterinary Science, 2023)
Bovine besnoitiosis is an emerging disease caused by the protozoa Besnoitia besnoiti that may have serious economic impact on affected farms. The fact that there is no effective vaccine nor treatment, along with the lack of consistent epidemiologic data, renders the implementation of preventive medicine and control strategies much harder. A cross-sectional serological assessment was performed to better understand the distribution and prevalence of this parasite in a large beef cattle farm in Portugal and to establish some epidemiological characteristics of bovine besnoitiosis. A random blood sampling of 450 animals from a farm that keeps around 2,000 cattle head was performed and sera submitted to an indirect immunofluorescent-antibody test (IFAT). Data on breed, age, sex and birthplace of the tested animals and their mothers, was recorded. The overall prevalence of positive animals was 16.89%, with significant differences between under one-year-old calves (4.8%) and adults (19.67%). A higher antibody prevalence was shown in animals 1-2 years and >7 years old, in Salers breed and in cows imported from France or whose mothers had come from this country. Calves under 1 year-old and crossbreed animals with ancestry born in the current farm, presented the lowest antibody prevalence. The most significant risk factors revealed were age (>7 years-old) and breed (Salers). Genetic studies should be carried out in order to confirm if indeed there is a breed susceptibility to bovine besnoitiosis. We suggest that similar studies should be performed across southern Europe to establish a strong epidemiologic data that would allow for a rigorous transnational control programs to be launched.